Analysis of Product Inventory Control using Continuous Review System (Q Method) and Periodic Review System (P Method) to Minimize Inventory Costs - Irwan Setiawan; Rofifah Rasul; Muhammad Rusman (Jurnal Rekayasa Sistem & Industri, 2023)
Store X is a store that sells muslim fashion products. There is a phenomenon that often occurs in one of StoreX's branches, such as the shortage of jetblack hijab products in stock. This phenomenon results in thecompany's loss of opportunity to gain profit and has an impact on high inventory costs. Based on this, it isknown that one of Store X’s branches does not yet have a good inventory system, so it is necessary to applyoptimal inventory methods and minimize inventory costs. This study uses a quantitative approach to datacollection methods of interviews, literature studies, and company historical data. The data analysis methodused is the SMA, WMA, and SES methods with each of the two conditions. As well as using the ContinuousReview System method (Q method) and the Periodic Review System method (P method) for the calculationof inventory policy and total inventory costs. Based on the results of the study, it was found that the Q methoddetermines the optimal ordering lot quantity and the point of having to reorder goods. This resulted in thestock in the warehouse always being replenished on time so that there were no excess or shortage of inventoryand customer requests could be fulfilled so that inventory costs could be minimized. Based on this statement,it is stated that the Q method is suitable for the company because it provides an optimal inventory policy andminimizes inventory costs by 5.90% or IDR 44,771,467 of company costs.